2018
DOI: 10.1097/mlr.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Examining Parental Medication Adherence as a Predictor of Child Medication Adherence in Pediatric Anxiety Disorders

Abstract: Parental medication adherence could help providers identify children at risk of nonadherence to inform the treatment decision, reduce unnecessary medication switches, and lead to broader effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…In the latter situation, a parent's mental health condition could lead to the recognition of the importance of outpatient treatment. 54 Findings reported by Jon-Ubabuco & Dimmitt Champion 66 and Bushnell et al 72 corroborate that hypothesis. The first study found that African American caregivers who struggled with mental health issues themselves were better able to recognize these issues in adolescents and were more predisposed to seek out MHS.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the latter situation, a parent's mental health condition could lead to the recognition of the importance of outpatient treatment. 54 Findings reported by Jon-Ubabuco & Dimmitt Champion 66 and Bushnell et al 72 corroborate that hypothesis. The first study found that African American caregivers who struggled with mental health issues themselves were better able to recognize these issues in adolescents and were more predisposed to seek out MHS.…”
Section: Discussionmentioning
confidence: 59%
“…Bushnell et al expanded the scope of the issue to how parents understood their overall health (by assessing their adherence to statin and antihypertension medication use) and the effect this had on adherence to their children's anxiety treatment, concluding that perceptions of the parent's own health and need for treatment could be an important predictor of child and adolescent treatment compliance overall. 72 Interventions occurring in EDs 42,50,53 and in initial inpatient treatment 25,51 were shown to improve treatment compliance. Several other studies have addressed the effects of ED interventions on the treatment compliance of adolescents and young people with SB.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study among children with anxiety disorders documented that treatment adherence was associated with the length of medication usage. 33 Possible reasons for a decline in the compliance with medication over a longer time period could be the lack of continuous or regular health education support.…”
Section: Compliance With Medicationmentioning
confidence: 99%
“…A review of studies on compliance with medication in children with epilepsy identified several environment-related factors influencing compliance with medication. 33,34 For example, three identified studies in the review documented that Score range of the multiple-choice questions was 0-2 support form medical and nursing staff was related to better adherence. Three other studies reported that better socio-economic status of the family would predict better compliance with medication.…”
Section: Compliance With Medicationmentioning
confidence: 99%
See 1 more Smart Citation